ERβ mediates sex-specific protection in the App-NL-G-F mouse model of Alzheimer’s disease - Aphrodite Demetriou; Birgitta Lindqvist; Heba G. Ali; Mohamed M. Shamekh; Mukesh Varshney; Jose Inzunza; Silvia Maioli; Per Nilsson; Ivan Nalvarte (Biology of Sex Differences)
Abstract Background Menopausal loss of neuroprotective estrogen is thought to contribute to the sex differences in Alzheimer’s disease (AD). Activation of estrogen receptor beta (ERβ) can be clinically relevant since it avoids the adverse systemic effects of ERα activation. However, very few studies have explored ERβ-mediated neuroprotection in AD, and no information on its contribution to the sex differences in AD exists. In the present study, we specifically explored the role of ERβ in mediating sex-specific protection against AD pathology in the App NL−G−F knock-in mouse model of amyloidosis, and if surgical menopause (ovariectomy) modulates pathology in this model. Methods We treated male and female App NL−G−F knock-in mice with the clinically relevant and selective ERβ agonist LY500307. A subset of the females was ovariectomized prior to treatment. Y-maze and contextual fear conditioning tests were used to assess memory performance, and biochemical assays such as qPCR, immunohistochemistry, Western blot, and multiplex immunoassays, were used to evaluate amyloid pathology. Results We found that Female App NL−G−F mice had higher soluble Aβ levels in cortex and hippocampus than males and more activated microglia. ERβ activation protected against amyloid pathology and cognitive decline in both male and female App NL−G−F mice. Although ovariectomy increased soluble amyloid beta (Aβ) in cortex and insoluble Aβ in hippocampus, as well as sustained neuroinflammation after ERβ activation, it had otherwise limited effects on pathology. We further identified that ERβ did not alter APP processing, but rather exerted its protection at least partly via microglia activation in a sex-specific manner. Conclusion Combined, we provide new understanding to the sex differences in AD by demonstrating that ERβ protects against AD pathology differently in males and females, warranting reassessment of ERβ in combating AD.